GROWTH PERFORMANCE AND HAEMATOLOGICAL PARAMETERS OF GROWING YANKASA RAMS FED VARYING PROPORTIONS OF GROUNDNUT HAULMS AND COWPEA SHELL IN DIETS - Maiyaki, U. S.; Abubakar, M.; Muhammad, A. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was conducted to evaluate the growth performance and haematological parameters of growing Yankasa rams fed varying proportions of cowpea shell and groundnut haulms in diets. A total of 20 Yankasa rams were assigned to five isonitrogenous dietary treatments (16% crude protein) formulated to include groundnut haulms and cowpea shell at varying proportions such that the two ingredients collectively contributed 40% of the diets. The experiment was conducted in a Completely Randomized Design, with five (5) treatments of four (4) animals each. The result indicated a significant (P<0.05) difference in daily feed intake (DFI) of the animals across the treatments. DFI for animals on diet 1 (1309.00 g/day), 5 (1342.00 g/day) and 2 (1262.00 g/day) were similar and significantly higher than those on the other treatments (1282.00 and 1288.00 g/day for treatments 3 and 4). Water intake (litres per day and litres per kg dry matter intake) of the rams fed the various diets indicated a non-significant difference between the means in both cases. The values of water intake (l/day) range from 1.99 for treatment 5 to 2.28 for those on treatment 1. The result of daily weight gain (DWG) revealed a highly significant (P<0.001) difference across the treatments. The mean value of the DWG for animals on treatment 1(125.86g/day) was significantly higher than those for the other diets, followed by those on treatment 5 (93.86 g/day) and 4 (81.14 g/day). Animals on treatments 2 (73.57 g/day) and 3 (79.29 g/day) recorded the least DWG values. All animals gained weight, which indicated that, the intake of energy and proteins were well above maintenance requirements. Feed conversion ratio (FCR) values of rams fed the test diets indicated a significant (P<0.05) difference across the treatments. Animals on treatment 1 gave the best FCR value (10.40) compared to those on the other diets. This was closely followed by those on treatments 4 (15.87) and 5 (14.30). Animals on treatments 2 (17.15) and 3 16.17 recorded the least FCR values. The results of haematological parameters indicated that most of the parameters were within the normal values recommended for sheep indicating that the animals were healthy. From the results of the current study, based on the higher weight gains of 125.86g/day, best feed conversion ratio of 10.40 and normal levels of haematological parameters, diet 1 (40% GH 0% CS) is recommended for growing Yankasa rams.